Failure mechanisms of kenaf/glass sandwich laminates subjected to low velocity impact loading. Issue 3 (June 2022) - Ahmad Nadzri, Seri Nur Zumaimi; Md Shah, Ain Umaira; Sultan, Mohamed Thariq Hameed; Safri, Syafiqah Nur Azrie; Shahar, Farah Syazwani; Basri, Adi Azriff
Stacking sequences of composite laminates have significant effects not only on the properties of composites but also on the types of damage occurred on the composites structure. The current study investigated the low velocity impact properties and the damage progression of kenaf core sandwich laminates in different layering sequence of fibre laminates. There were three different sequences of kenaf (K) and glass (G) fibre reinforced unsaturated polyester composites, that is, G/K/G hybrid, G/K/K hybrid and K/K/K composites, which were fabricated using hand lay-up method. The layer of gelcoat provided a protective layer and finishing to the composite. The composites experienced the low velocity impact at three different energy levels which were 5 J, 10 J and 15 J. Through the research, a diamond shape matrix cracking was exhibited on the gelcoat surface. The main failure mode that occurred on the specimen during the low velocity impact was matrix cracking, fibre breakage, delamination and fibre pulled-out. From the results, G/K/G hybrid resisted the highest impact energy which is up to 10 J and G/K/K hybrid resisted up to 5 J. Meanwhile K/K/K composite failed to resist any of designated energy. Therefore, it can be suggested that G/K/G hybrid composites had shown good performance in low velocity impact properties to be used as the bus bumper material.